2008
DOI: 10.1253/circj.cj-08-0291
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Indicators of Stress Response and Postoperative Inflammatory Complications in Patients Undergoing Off-Pump Coronary Artery Bypass Surgery A Prospective Observational Study

Abstract: Background Little has been published regarding the association between perioperative stress response and clinical outcomes after off-pump coronary artery bypass surgery (OPCAB). The role of perioperative stress response in postoperative inflammatory complications (PIC) in patients undergoing OPCAB was assessed. Methods and ResultsThe study cohort consisted of 100 patients who underwent elective OPCAB over a 5-month period. Anesthetic management was standardized and blood samples were collected before surgery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
2
9
0
2
Order By: Relevance
“…[23][24][25] In our trial, WBC count and CRP concentration rose continuously to maximum concentrations on postoperative days 2 and 3, respectively, and were showing a trend toward baseline levels by postoperative day 4. Conversely, fibrinogen levels declined on postoperative day 1 before continuously rising through postoperative day 4.…”
Section: Baseline and Postoperative Values For Inflammatory Mediators Asupporting
confidence: 50%
“…[23][24][25] In our trial, WBC count and CRP concentration rose continuously to maximum concentrations on postoperative days 2 and 3, respectively, and were showing a trend toward baseline levels by postoperative day 4. Conversely, fibrinogen levels declined on postoperative day 1 before continuously rising through postoperative day 4.…”
Section: Baseline and Postoperative Values For Inflammatory Mediators Asupporting
confidence: 50%
“…So, it has predicted role that it's preoperative elevation as correlation with high morbidity and mortality rate. Patients undergoing heart surgery under CPB frequently experience systemic reactions that causes postoperative morbidity and prolonged hospital stay [8]. Some studies demonstrated increased preoperative levels of CRP and adverse events [10]- [13].…”
Section: Discussionmentioning
confidence: 99%
“…CRP is a plasma active reactant phase protein (normal: 0 -5 mg/L) that increases approximately in every type of inflammation and returns rapidly to normal level in recovery time [8]. In various studies, specificity and sensitivity of test had been evaluated in diagnosis and management of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This can be particularly challenging in patients undergoing cardiothoracic surgery especially in those who are exposed to extracorporeal circulation. Patients undergoing cardiopulmonary bypass (CPB) often experience profound physiologic responses to the extracorporeal circulation with alterations in the hypothalamic-pituitary-adrenal access as well as activation of the inflammatory system [16,17]. Glucocorticoids are required for normal cardiovascular reactivity to angiotensin II, epinephrine, and norepinephrine [12].…”
Section: Discussionmentioning
confidence: 99%